Characterization of mobile genetic element-associated genes in methicillin-resistant Staphylococcus species - Abdul Rachman, Abdul Rahim (2017)
Methicillin resistance (MR) in Staphylococcus species was believed to be carried through mobile genetic elements (MGE) called as Staphylococcal Chromosomal Cassette mec(SCCmec) and transmitted into S. aureus (SA) from other Staphylococcus sp. resulting in emergence of MRSA. Thus, the understanding of SCCmec in a variety of Staphylococcus species is crucial in order to understand on how the process is being facilitated in the organisms. Hence, this study was conducted to characterize the multi-genetic element associated genes for the understanding of methicillin resistant determinant in different Staphylococcus species. Biochemical test, 30 μg cefoxitin diffusion disc test, cefoxitin E-test, mec,bla complexes,IS431 and IS1272 distributions, Pbp2a and β-lactamase assays were conducted to characterize the phenotypic and genotypic characteristics of MRSA and MRCoNS available in laboratory collection. Isolates which carry mecA gene were subjected to typing methods; SCCmec typing, MLST, dru typing and PCR-RFLP of gap genes. Various bioinformatics analysis; phylogenetic tree construction, multiple sequence alignment and protein sequence analysis were conducted to observe the correlation of various factors toward methicillin resistance determination in MRSA and MRCoNS. Sixteen MRSA and nineteen MRCoNS were identified by biochemical tests, 30 μg cefoxitin antibiotic disc susceptibility test and mecA gene screening. Twenty nine isolates had a complete mecAgenes (~2.1 kb), incomplete mec regulator (negative or truncated) and positive PBP2a assay for both MRSA and MRCoNS. Only MRCoNS SC177 isolate with cefoxitin MIC of 32 μg/ml carries complete mec complex. All MR isolates (n=35) carried IS431,whereas more MRCoNS (n=13) carried IS1272 compared to MRSA (n=2). Thirty-one of thirty-five methicillin resistant isolates that carried complete bla complex (blaZ,blaRI, blaI) with 10 MRSA produce strong β-lactamase and cefoxitin MIC of ≥12 μg/ml. Only 4 MRCoNS with cefoxitin MIC of ≤8 μg/ml produce strong β-lactamase. The diversity of blaZ gene was demonstrated by phylogenetic analysis and unusual amino acid mutation at position 145 of MRSA SA60 isolate may compromise its β-lactamase activity with low cefoxitin MIC level (2 μg/ml). For SCCmec typing, 15 isolates (MRSA=11; MRCoNS=4) were categorized as non-typeable, 12 isolates (MRCoNS=12) as SCCmec type IV, 4 isolates (MRSA=2; MRCoNS=2) as SCCmec type I, 3 isolates (MRSA=3) as SCCmec type II and 1 isolate (MRCoNS=1) as SCCmec type V. Dru typing was based on PCR amplification of dru region in SCCmec structure and drusequence analysis for dru type determination. Result showed that, 32 isolates (MRSA=13; MRCoNS=19) from 38 MR Staphylococcus isolates were positive for druregion amplification by using PCR. Three dru types were detected which are dt11c (MRSA=12; MRCoNS=5), dt10a (MRSA=1; MRCoNS=12) and dt7a (MRCoNS=1). For RFLP analysis, all isolates were positive for gap gene amplification by using PCR and produce 11 different gene sizes after digestion with AluI restriction enzyme. For MLST, 6 sequence types (ST2, ST5, ST57, ST59, ST72, ST193) were detected among MRCoNS while 4 sequence types (ST15, ST88, ST188, ST508) were detected among MRSA. As a conclusion, isolates that carry complete mecA gene were largely consistent with the expression of Pbp2a. However, there is no clear correlation of mecregulator genes in relation to cefoxitin-MIC in both methicillin resistant (MR) Staphylococcusspecies. On the other hand, various expression level of β-lactamase may correlate with cefoxitin-MIC level in MRSA as compared to MRCoNS. Besides that, dru typing and gap-RFLP showed obvious distinct pattern between MR with MIC ≥8 μg/ml and MR with MIC <8 μg/ml. Commonly, MR isolated from carriage had sequence type (ST) originated from community. However, certain sequence type (ST) of MR from carriage may originated from healthcare or animals and disseminated into community.